Resveratrol Attenuates Allergic Asthma and Associated Inflammation in the Lungs Through Regulation of miRNA-34a That Targets FoxP3 in Mice - Alharris, Esraah; Alghetaa, Hasan; Seth, Ratanesh; Chatterjee, Saurabh; Singh, Narendra P.; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Immunology, 2018)
Asthma is a chronic inflammatory disease of airways mediated by Th2 cells involving complex signaling pathways. Although resveratrol has previously been shown to attenuate allergic asthma, the role of miRNA in this process has not been studied. We investigated the effect of resveratrol on ovalbumin-induced experimental allergic asthma in mice. To that end, BALB/c mice were immunized with ovalbumin (OVA) intraperitoneally followed by oral gavage of vehicle (OVA-veh) or resveratrol (100 mg/kg body) (OVA-res). On day 7, the experimental groups received intranasal challenge of OVA followed by 7 days of additional oral gavage of vehicle or resveratrol. At day 15, all mice were euthanized and bronchioalveolar fluid (BALF), serum and lung infiltrating cells were collected and analyzed. The data showed that resveratrol significantly reduced IL-5, IL-13, and TGF-β in the serum and BALF in mice with OVA-induced asthma. Also, we saw a decrease in CD3+CD4+, CD3+CD8+, and CD4+IL-4+ cells with increase in CD4+CD25+FOXP3+ cells in pulmonary inflammatory cell infiltrate in OVA-res group when compared to OVA-veh. miRNA expression arrays using lung infiltrating cells showed that resveratrol caused significant alterations in miRNA expression, specifically downregulating the expression of miR-34a. Additionally, miR-34a was found to target FOXP3, as evidenced by enhanced expression of FOXP3 in the lung tissue. Also, transfection studies showed that miR-34a inhibitor upregulated FOXP3 expression while miR-34a-mimic downregulated FOXP3 expression. The current study suggests that resveratrol attenuates allergic asthma by downregulating miR-34a that induces increased expression of FOXP3, a master regulator of Treg development and functions.